Terahertz Electronic Source Based on Spoof Surface Plasmons on the Doubly Corrugated Metallic Waveguide - Yong-Qiang Liu; Chao-Hai Du; Pu-Kun Liu (IEEE Transactions on Plasma Science, 2016)
Spoof surface plasmons (SSP) has become an active research topic in microwave and terahertz (THz) spectrum since its extraordinary optical and physical properties. The strong near field of SSP mode on the corrugated metal surfaces makes it especially attractive for developing a THz electronic source. A THz electronic source based on the efficient generation of SSP modes on the doubly corrugated metallic waveguide is proposed and studied in this paper. The analytical dispersion relations of SSP modes are obtained based on a modal expansion method and the field profiles of SSP modes are also presented by the finite integration method. Besides, the interaction between SSP and injected electron beam is modeled and implemented by particle-in-cell (PIC) simulation based on finite difference time domain algorithm. The gap size between the doubly corrugated metal surfaces can significantly influence the output power and PIC simulation results reveal that output power can be increased from 272 mW to 36.5 W when the gap size decreases from 90 to 40 μm at the frequency near 1 THz by the 19.55 kV, 1 A injected electron beam within 4.5-mm interaction length. The dependencies of the output performance on electron beam parameters are also investigated and we find that there is an optimized beam voltage for the given operation frequency. Various electron beams of pulse and direct current electron beam are studied and we find that half pulsewidth of periodical electron beam is more preferable than other emissive shape of injected electron beam for the given structure. Our studies on the efficient generation of SSP modes on the doubly corrugated metallic waveguide may provide a new way to develop THz electronic sources.